Polymorphic loci of the ESR1 gene are associated with the risk of developing preeclampsia with fetal growth retardation - O. V. Golovchenko; M. Yu. Abramova; I. V. Ponomarenko; M. I. Churnosov (IRBIS LLC, 2020)
Aim: to analyze the association of polymorphic loci rs2234693, rs9340799, and rs3798577 of the ESR1 gene with the development of preeclampsia (PE) with fetal growth retardation (FGR) and to consider their regulatory potential.Materials and Methods. The present study was performed on a sample of 400 women: 76 pregnant women with PE and FGR and 324 with a physiological course of pregnancy. Three polymorphic loci of the ESR1 gene (rs2234693, rs9340799, and rs3798577) were genotyped. Functional effects of polymorphic loci were evaluated using the online programs HaploReg (epigenetic effects) and GTExportal (relation to gene expression).Results. The development of PE and FGR is associated with the G allele and GG genotype rs9340799 of the ESR1 gene (OR = 1.38; pperm = 0.04 and OR = 2.00, pperm = 0.04 respectively), the T allele rs3798577 of the ESR1 gene (OR = 1.46; pperm = 0.01), and the TG haplotype of the polymorphic loci rs2234693-rs9340799 of the ESR1 gene (OR = 2.08; pperm = 0.009). Polymorphic loci rs2234693, rs9340799 ESR1 gene and rs3798577 have important functional significance in the organism are evolutionary conservative region of DNA, affect affinnity regulatory DNA motifs by 8 transcription factors and gene expression ESR1 in the thyroid gland, located in the region of promoters and enhancers, the region of hypersensitivity to DNase 1 in various organs and tissues, has important pathogenetic importance for the development of PE and FGR.Conclusion. Polymorphic loci rs2234693, rs9340799 and rs3798577 of the ESR1 gene are associated with the development of PE and FGR.